Assessment of the exposure to Benzo(a)Pyrene (BaP) contained in sardines (Clupeidae) consumed by the Ivorian adult in the area of Abidjan - Ake-Assi, Y.; Anon, N.; Kouamé, P.; Bonfoh, Bassirou; Biego, G.H.M. (2014)
In Côte d’Ivoire, fish products provide a substantial part of needs for animal proteins. Yet, owing to the different processing and preservation procedures used, neoformed molecules appear in the flesh of fish sold for consumption. Therefore, it is necessary to check the quality of the fish obtained from traditional processing procedures. This check involves regular determination of the levels of Polycyclic Aromatic Hydrocarbons (PAH) which cause some diseases such as cancer. This study aims to assess the contamination level of BaP present in smoked fish from the different production sites of the area of Abidjan so as to estimate, in the Ivorian adult, the intake of this neoformed contaminant during processing. For that purpose, 248 samples of fresh and smoked fish were collected. The calculation of the exposure from the determination of BaP in the samples of fish collected was made possible thanks to a High Performance Liquid Chromatograph (Adept), equipped with a UV-visible dectector (CE 4200 CECIL), a pump (CECIL CE 4104), an automatic injector (SPARK Optimas) and a column of Prevail C18 type (150 mm x 4.6 mm x 5 µm). The results revealed the presence of BaP in highly variable concentrations, between 0.65 and 510.3 µg/kg in the samples of fish tested. The estimated intake for the average Ivorian is 10.69 ng/kg BW/d for fresh fish and 47.4 ng/kg BW/d for smoked fish. That intake is at least twice the Toxicity Reference Value (5 ng/kg BW/d). In view of the characteristics of this danger, it is urgent to sensitise, on a larger scale, not only the actors and the consumers but also the competent authorities in charge of the safety control of foodstuffs.